Influence of Environment and Genetics on Reproductive Health of Twins - Jahanfar, Shayesteh (2007)
Reproductive health is a dynamic part of our lives with a broad spectrum of events. Study of twins can assist to investigate the relationship between environmental and hereditary causes of reproductive diseases, which would otherwise be difficult if not impossible to study. High concordance between twin pairs suggests a strong influence for genetic factors, whereas low concordance indicates a weak influence. Preventive measures can be taken into consideration for those who are at risk of environmental influences if and only when the role of genetic is minor even though gene therapy may minimize the occurrence of genetic disease. This cross-sectional descriptive study of reproductive health of twins investigated the heritability of qualitative and quantitative measured variables related to reproductive events or behavior of adult twins. Subjects included 156 identical and 110 non-identical twins, 15 years and above who were living in urban areas of Iran and Malaysia. Basic and modern genetic analysis was adopted. Maximum likelihood analysis and model fitting analysis suggested that birth weight, weight, height, age of menarche, premenstrual symptoms, acne, hirsutism, baldness and infertility are mostly determined by genetic factors while characteristics of menstruation were more likely under the influence of environmental factors. Classical genetic analysis using Falconer’s formula suggested higher similarity between monozygotic twins than dyzyotics in relation to reproductive behaviors such as age of first pregnancy and number of pregnancies. Probandwise concordance rate analysis showed higher similarity between identical twins in adopting correct reproductive behavior such as undergoing pap smear and using family planning techniques. Model fitting analysis for the ACE model supported these findings. Same-sex twins had a higher risk of congenital abnormality, gynecological problem, and irregular menstruation than opposite sex twins. Other reproductive events were not found to be significantly different between the two groups indicating that hormonal transition from male to female may not be a valid explanation for reproductive ill health. Birth weight was not found to affect reproductive morbidity during adult life as frequency of reproductive event was found to be higher among low birth weight twins compared with normal weight twins. This finding is not consistent with fetal origin hypothesis or thrifty gene hypothesis. Reproductive ill-health influenced by environmental factors may be minimized using careful primary care evaluation, early detection and prevention while genetic predisposition can be monitored for those variables under genetic influence. Early reproductive health consultation for adolescents is recommended to avoid complications of reproductive ill-health.